Anti-tumor enhancement of Fei-Liu-Ping ointment in combination with celecoxib via cyclooxygenase-2-mediated lung metastatic inflammatory microenvironment in Lewis lung carcinoma xenograft mouse model. Issue 1 (December 2015) - Liu, Rui; Zheng, Honggang; Li, Weidong; Guo, Qiujun; He, Shulin; Hirasaki, Yoshiro; Hou, Wei; Hua, Baojin; Li, Conghuang; Bao, Yanju; Gao, Yebo; Qi, Xin; et al.
Abstract Background Fei-Liu-Ping (FLP) ointment is an oral prescription medication that has been widely applied to treat lung cancer patients in China. Regulation of the metastatic microenvironment is an important therapeutic approach for prevention and treatment of tumor recurrence and metastasis. The advantage of Traditional Chinese Medicine management of lung cancer lies in the prevention of recurrence and metastasis. Our previous study has demonstrated that FLP ointment could regulate lung inflammatory microenvironment in vitro. However, the effects of FLP on the tumor microenvironment in vivo are still poorly understood. The objective of this study is to investigate the effect of FLP alone or in combination with celecoxib in the prevention of lung cancer progression by Cyclooxygenase (Cox)-2 mediated tumor inflammatory microenvironment in vivo. Methods 120 Lewis lung carcinoma xenograft mice were divided equally into four groups: vehicle, FLP, celecoxib, and FLP plus celecoxib. The dynamic growth of the xenografted tumors was observed using an in vivo fluorescence imaging system. Mice were sacrificed on day 14, day 21, and day 28, and tumor specimens and lung tissues were harvested to detect the metastasis-associated protein expression. Results Tumor inhibition rate was 15.4, 44.2, 47.4 % at day 14, 37.3, 34.7, 61.5 % at day 21, and 15.5, 10.3, 32.5 % at day 28 after treatment of FLP, celecoxib, and FLP plus celecoxib, respectively. Upon treatment of FLP and celecoxib together, lung metastasis rate was 30 % (8 metastatic nodules) lower than other groups. FLP inhibited Cox-2 expression in a time-dependent manner. Moreover, FLP inhibited N-cadherin, matrix metalloproteinases (MMP)-9, and Vimentin expression. Treatment of FLP in combination with celecoxib was more effective than FLP or celecoxib alone in inhibiting vascular endothelial growth factor, platelet-derived growth factor receptors β, microsomal Prostaglandin E synthase-1, MMP-2, MMP-9, N-cadherin, and Vimentin expression, but increased E-cadherin expression. Conclusions FLP inhibited tumor growth and metastasis in a Lewis lung xenograft mice model through the Cox-2 pathway. FLP in combination with celecoxib enhanced the antitumor growth and anti-metastasis effects. Traditional Chinese herbs combined with anti-inflammatory drugs might offer a promising strategy to prevent tumor metastasis.